Viability test of fish scale collagen (Oshpronemus gouramy) on baby hamster kidney fibroblasts-21 fibroblast cell culture - Chiquita Prahasanti; Denny Tri Wulandari; Noer Ulfa (Veterinary World, 2018)
Aim: This study aims to examine the toxicity of collagen extracted from gouramy fish scales (Oshpronemus gouramy) by evaluating its viability against baby hamster kidney fibroblasts-21.